2023
DOI: 10.3233/jad-210326
|View full text |Cite
|
Sign up to set email alerts
|

Increased Functional Connectivity of the Precuneus in Individuals with a Family History of Alzheimer’s Disease

Abstract: Background: First-degree relatives of individuals with late-onset Alzheimer’s disease (AD) have increased risk for AD, with children of affected parents at an especially high risk. Objective: We aimed to investigate default mode network connectivity, medial temporal cortex volume, and cognition in cognitively healthy (CH) individuals with (FH+) and without (FH-) a family history of AD, alongside amnestic mild cognitive impairment (aMCI) and AD individuals, to determine the context and directionality of dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Hitherto, compelling evidence has suggested that the disease course of AD is more likely to be an inverted U-shaped pattern than a continuous decline, meaning that people may experience a better functional stage before the decline of cognitive ability (Corriveau-Lecavalier et al, 2020 ). Findings from functional MRI-based studies revealed that individuals with an early stage of dementia or who were cognitively normal but at a higher risk of developing dementia (carrying the APOE4 allele or having a family history of dementia) presented with greater brain activation, supporting this inverse quadratic hyperactivation hypothesis (Bookheimer et al, 2000 ; Burggren et al, 2002 ; Bondi et al, 2005 ; Wierenga et al, 2013 ; Green et al, 2023 ). These altered hyperactivations in MRI may present corresponding functional changes and better performance during antisaccade trials.…”
Section: Discussionmentioning
confidence: 95%
“…Hitherto, compelling evidence has suggested that the disease course of AD is more likely to be an inverted U-shaped pattern than a continuous decline, meaning that people may experience a better functional stage before the decline of cognitive ability (Corriveau-Lecavalier et al, 2020 ). Findings from functional MRI-based studies revealed that individuals with an early stage of dementia or who were cognitively normal but at a higher risk of developing dementia (carrying the APOE4 allele or having a family history of dementia) presented with greater brain activation, supporting this inverse quadratic hyperactivation hypothesis (Bookheimer et al, 2000 ; Burggren et al, 2002 ; Bondi et al, 2005 ; Wierenga et al, 2013 ; Green et al, 2023 ). These altered hyperactivations in MRI may present corresponding functional changes and better performance during antisaccade trials.…”
Section: Discussionmentioning
confidence: 95%
“…Our imaging findings went in either direction, an increase or a decrease of functional connectivity within networks. A classical neurobiological interpretation of decreases and increases of connectivity are network disruption in the former case and compensatory mechanisms of brain plasticity in the latter case [62][63][64]. Main contribution to this interpretation comes from longitudinal studies, which documented an increase of functional connectivity passing from mild cognitive impairment status to dementia [65][66][67].…”
Section: Discussionmentioning
confidence: 99%